When Motivations Meet Affordances: News Consumption on Telegram. (19th May 2021) - Lou, Chen; Tandoc Jr., Edson C.; Hong, Li Xuan; Pong, Xiang Yuan (Brenda); Lye, Wan Xin (Rachelle); Sng, Ngiag Gya (Trisha)
ABSTRACT: Guided by the Uses and Gratifications approach and the concept of affordances, this study sought to understand the phenomenon of news consumption on an emerging messaging platform— Telegram, wherein users consume concise pieces of news spontaneously through mobile devices or web interfaces. Based on in-depth interviews with 29 interviewees, this study identified user motivations underpinning news consumption on Telegram and platform affordances that facilitate such behavior. This study identified (1) socialization, (2) information, and (3) increasing demand for efficiency as key motivations. We also found that news consumption is facilitated by Telegram 's affordances like customizability, increasing accessibility, aesthetics, and simultaneity of activities. The findings advanced extant literature on user motivations for news consumption on new technologies and research on affordances. More importantly, this research integrates an affordance-based framework when studying motivations underlying user behaviors on new technologies.